Peran Ekstrakurikuler Taekwondo Dalam Meningkatkan Kecerdasan Kinestetik Anak Usia Dini: Sebuah Tinjauan Literatur - Risa Arosyidah; Gilar Gandana; Risbon Sianturi (Indonesian Publication Center, 2024)
This study aims to highlight the role of Taekwondo extracurricular activities in enhancing the kinesthetic intelligence of early childhood. The method used in this study is a literature review, which involves collecting and analyzing data from various academic sources over the past seven years. Five articles were identified as primary studies from the search results. These articles were analyzed, and the findings were narrated to discuss the benefits of Taekwondo on kinesthetic intelligence. The results indicate that Taekwondo extracurricular activities play a significant role in improving motor skills, fostering positive psychological impacts, enhancing social development, and promoting physical fitness in early childhood. These findings provide a foundation for developing extracurricular programs to support the holistic growth of children. The practical implications of this study underscore the importance of integrating physical activities such as Taekwondo into early childhood education curricula to maximize children's potential and develop their kinesthetic intelligence. This study highlights the importance of integrating Taekwondo into early childhood education to optimize their kinesthetic intelligence potential.